Penyuluhan Kesehatan Dan Pemeriksaan Hemoglobin (HB) Dalam Upaya Pencegahan Anemia Pada Ibu Hamil - Delfina, Rina; Maryani, Deni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Maintaining the mother's health during pregnancy is one of the main keys to the health of the next generation, because the mother will give birth to a healthy generation if the mother's health during pregnancy is good and without problems. The thing that must be maintained by pregnant women is to get adequate nutrition for themselves and the fetus they are carrying. One of the problems that often arises in pregnant women is anemia. Anemia in pregnant women can increase the risk of low birth weight (LBW) babies, premature birth, maternal and infant deaths and stunting (short children). Various efforts have been made to control anemia in pregnancy, but the prevalence is still high. One of the efforts that can be made to prevent anemia in pregnant women is to check hemoglobin and increase the mother's knowledge about anemia and its management, so that the mother understands her health condition during pregnancy. The aim of this community service activity is to screen for anemia in pregnant women. The benefit of this activity is that pregnant women know their hemoglobin levels and get information about anemia during pregnancy and its management.